Aplikasi ZPT Atonik pada Berbagai Konsentrasi terhadap Pertumbuhan, Perkembangan, dan Kualitas Buah Lengkeng (Dimocarpus longan) - Linda, Linda Aznida; Juhan, Muhammad (Program Studi Agroteknologi, 2023)
This study aims to determine the best concentration of atonic PGR to increase the quantity and quality of longan fruit. People's doubts about the quality of locally produced longan fruit as a substitute for imported fruit must be answered immediately by presenting domestically produced longan fruit that has fruit characteristics that suit consumer tastes and with better quality. The role of the auxin hormone on fruit growth and development is to increase fruit volume. One of the biostimulants that can be used as growth regulators is atonik. This research was carried out in Pancakarya Village, Ajung District, Jember Regency which was carried out from January 2022 to March 2022 with an altitude of 50 m above sea level. This study used a non-factorial Randomized Block Design (RAK), with 6 different spraying treatments, repeated 4 times, the number of research objects 24. The treatments studied were atonic concentrations, namely: L0 = Control, L1 = Concentration of 20 ppm, L2 = Concentration of 30 ppm , L3 = Concentration of 40 ppm, L4 = Concentration of 50 ppm, L5 = Concentration of 60 ppm. The data collected was analyzed for variance (Anova), if it was significantly different, then proceed with the BNT test at the 5% level. In determining the fruit to be sprayed using a random system. The results showed that the concentration of atonic PGR in all treatments gave no significant difference, but the concentration of atonic PGR in treatment L2 (30 ppm) gave optimal results for the vertical diameter of the fruit, the horizontal diameter of the fruit, the sugar content of the fruit, and the resistance of the fruit bunches.